PENYERAPAN TENAGA KERJA DI SUMATERA UTARA TAHUN 2016-2020 - FIRSTY RAMADHONA AMALIA LUBIS; AGNES LINTANG KUSWARI; NURUL AZIZAH AZ ZAKIYYAH (LP2MTBM MAKARIOZ, 2022)
Regional Original Income is also a factor that has an influence on employment absorption. PAD can be used as a measure to assess regional economic conditions and community welfare. The number of workforce is the highest compared to the provinces on Sumatra Island in 2016-2020, of course North Sumatra Province also requires a larger number of jobs. The research objective was to analyze the relationship between employment and several independent variables, namely GRDP, UMK, PAD, and population. This research was conducted in 30 regencies and cities in North Sumatra Province in the period 2016 - 2020. The results of this study indicate that the best model used is the Fixed Effect Model. The results showed that the GRDP variable had a positive and significant effect on employment absorption. The UMK, PAD, and population variables have no significant effect on employment.